Future directions and management of liquid biopsy in non-small cell lung cancer - Alessia Maria Cossu; Marianna Scrima; Angela Lombardi; Anna Grimaldi; Margherita Russo; Alessandro Ottaiano; Michele Caraglia; Marco Bocchetti (Open Exploration Publishing Inc., 2020)
Lung cancer represents the world's most common cause of cancer death. In recent years, we moved from a generic therapeutic strategy to a personalized approach, based on the molecular characterization of the tumor. In this view, liquid biopsy is becoming an important tool for assessing the progress or onset of lung disease. Liquid biopsy is a non-invasive procedure able to isolate circulating tumor cells, tumor educated platelets, exosomes and free circulating tumor DNA from body fluids. The characterization of these liquid biomarkers can help to choose the therapeutic strategy for each different case. In this review, the authors will analyze the main aspects of lung cancer and the applications currently in use focusing on the benefits associated with this approach for predicting the prognosis and monitoring the clinical conditions of lung cancer disease.